Surface Patterns for Drag Modification in Volleyballs - Sungchan Hong; Takeshi Asai; Byung Mook Weon (Applied Sciences, 2019)
Surface patterns on objects are important in aerodynamics. We show how surface patterns on volleyballs modify their aerodynamic performances. Conventional volleyballs with six panels show different aerodynamic characteristics along transverse and diagonal directions. Interestingly, isotropic surface patterning with hexagons or dimples enables us to achieve isotropic aerodynamics. This result gives insight into surface-mediated flight controls of projectiles through resisting fluid media.